Crystalline phases and oxygen permeation properties of mixed conductive (La, Ca)FeO3-δ. Issue 4 (April 2019) - Kagomiya, Isao; Murayama, Tomoki; Tsunekawa, Kyosuke; Kakimoto, Ken-ichi; Ogura, Yusuke
Abstract: A typical mixed conductive oxide with high oxygen permeability is La0.6 Sr0.4 Co0.2 Fe0.8 O3- δ (LSCF), which is applicable to oxygen separation membrane and to cathodes for solid oxide fuel cells. However, Sr and Co included in the LSCF lower its stability when kept at elevated temperatures. La1- x Ca x FeO3- δ (LCF) is a good candidate of mixed conductive oxides with no Sr and Co ions. This study investigated systematic details of crystalline phase, electrical conductivity, and oxygen permeability as functions of the Ca content in the LCF. The x = 0.3–0.4 samples with perovskite structure reveal higher electrical conductivity and higher oxygen permeation flux J O2 among the investigated LCF. Particularly, the J O2 of the x = 0.35 and 0.4 are higher than that of the LSCF, proposing that the samples replace the LSCF. Larger specific free volumes in x = 0.3–0.4 are a possible main reason for higher vacancy mobility, resulting in higher J O2 .